Smoothed particle hydrodynamics and continuous surface cap model to simulate ice rubble in punch through test - Patil, Aniket; Sand, Björnar; Fransson, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2015)
Recent trend in computational mechanics shows considerable development of numerical methods to simulate discrete materials such as ice rubble. Ice rubble has highly nonlinear behavior and to simulate shear properties requires a new numerical method. An attempt has been made to simulate a punch through test using the Lagrangian mesh-free partial based method formulation known as smoothed particle hydrodynamics. A newly implemented material model in LS-Dyna called the continuous surface cap model has been used in this simulation. A continuous surface cap model based on a combination of elastic-plastic and continuum damage mechanics formulation is used as constitutive model for ice rubble. The material model parameters are chosen to get best fit to test load displacement curve. A brief overview of the smoothed particle hydrodynamics is given. Finally, the results from simulations have compared with experimental results. Godkänd; 2015; 20150926 (anipat)